PENGARUH CITRA MEREK, KESADARAN MEREK, DAN PERSEPSI KUALITAS JASA TERHADAP MINAT BELI PRODUK JASA UMROH PT. SILVER SILK TOUR & TRAVEL PEKANBARU - Tria Agustin Panggawati Nurcahyani; Okta Karneli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research was conducted at PT. Silver Silk Tour & Travel Pekanbaru located at Kaharuddin Nasution road No.77, Simpang Tiga Pekanbaru. The problem in this research is the target of umroh congragetion have not achieve for last five years, this is suspected existence of problem at purchase intention.The purpose of this study is to determine the influence of brand image, brand awareness, and perceived service quality to purchase intention products umroh PT. Silver Silk Tour & Travel Pekanbaru. In this research the method used is descriptive quantitative with SPSS program. The sample of this study as many as 100 people from the population amounted to 4,217 obtained from the calculation of Slovin formula. Data obtained from the results of further questionnaires processed for later tested through SPSS 23. Testing data analysis using simple linear regression analysis method and multiple. The result of multiple linear regression analysis from this research is Y = 5,032 + 0,130X1 + 0,236X2 + 0,315X3.The research that has been done shows that the responses of respondents to the brand image, brand awareness, and perceived service quality in the category agree while in purchase intention is in the category quite agree. While t-test that has been done indicate that variable of brand image, brand awareness, and perceived service quality partially have significant effect to buying interest. F-test results show that simultaneously brand image, brand awareness, and perceived service quality have significant effect to purchase intention. As for the calculation of coefficient of determination (R2) obtained Adjusted R Square value of 0,716. This shows that the brand image, brand awareness, and perceived service quality give 71,6% influence to purchase intention of umroh service product PT. Silver Silk Tour & Travel Pekanbaru, while the remaining 28,4% influenced other variables not included in this study.Keywords: Brand Image, Brand Awareness, Perceived Service Quality, and Purchase Intention